Mass Media and Religious Sentiment (A Discourse Analysis of Newspapers in Medan City) - Muhammad Thariq (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The study in this study used a discourse text analysis model to find out and explain the positions of three wary, Analysis and Sinar Indonesia Baru (SIB) newspapers in presenting the issue of the collapse of Al-Ikhlas Mosque at Timor Medan throughout 2012. This study also wanted to know the policy process media in determining one  news that will be presented to the reader including determining the issue, title, content of news, paragraphs, placement of news and news sources, especially related to the presentation of the news of the mosque's collapse. The goal is to look at the three newspaper mechanisms examined in producing news, journalists' relations with the media and media editors managing the news. The unit of analysis studied is news of events / hard (straight news / hard news) and news of interviews or analysis (news analysis). Researchers used the main theories of media discourse structure, media construction and media cognition from van. This research was carried out with three steps namely text, social cognition and context. In the text study, the researcher used two methods: analyzing the content with quantitative-descriptive and analyzing the framing of Robert Entmann. From the results of news framing, researchers conducted an in-depth interview with the editor in chief / editor of each newspaper studied to uncover and strengthen the results of the study as in the van Dijk model media text analysis phase. Interviews were conducted to determine the editorial / journalist's social cognition processes in the wary, Analysis and Sinar Indonesia Baru newspapers in constructing and interpreting the news of the collapse of the Al-Ikhlas Mosque. The results obtained from the three newspapers about the study were discourses framed by three newspapers about the news of the collapse of the Al-Ikhlas Mosque which had a difference: first, the wary  Daily expressed the truth with the background of the case problem so that it clearly showed its attitude against the mosque collapse. whereas Analysis and Sinar Indonesia Baru are more "safe looking". Secondly, the Daily wary, Analysis, and Sinar Indonesia Baru in constructing the collapse of the Al-Ikhlas mosque are strongly influenced by the background of the newspaper and its readers, and the editor's interpretation is influenced by religious and ethnic sentiments of the newspaper owner's background to strengthen the wary (Islam) Daily ideology. Analysis (ethnic Chinese) and Sinar Indonesia Baru (Christians) in the midst of the community which ultimately makes inconsistencies in the meaning and delivery of messages from the reality of the destruction of the Al-Ikhlas Mosque to the reader.